2019
DOI: 10.3390/bioengineering6010013
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from the Protozoa Acanthamoeba castellanii: Their Role in Pathogenesis, Environmental Adaptation and Potential Applications

Abstract: Extracellular vesicles (EVs) are membranous compartments of distinct cellular origin and biogenesis, displaying different sizes and include exosomes, microvesicles, and apoptotic bodies. The EVs have been described in almost every living organism, from simple unicellular to higher evolutionary scale multicellular organisms, such as mammals. Several functions have been attributed to these structures, including roles in energy acquisition, cell-to-cell communication, gene expression modulation and pathogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 108 publications
2
25
0
Order By: Relevance
“…Besides, in Dictyostelium discoideum, another free-living amoeba, the results of several studies raised the hypothesis of the participation of EVs in cell-to-cell communication [48,49]. Regarding Acanthamoeba, as mentioned before, there are two recent studies that demonstrated the production of EVs by trophozoytes of A. castellanii under homeostasis and nutritional stress and characterized their protein content [34,35]. The authors determined the lipid and protein content of these vesicles secreted by the amoebae incubated at 28 • C, temperature in which amoebae behave as free-living organisms.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Besides, in Dictyostelium discoideum, another free-living amoeba, the results of several studies raised the hypothesis of the participation of EVs in cell-to-cell communication [48,49]. Regarding Acanthamoeba, as mentioned before, there are two recent studies that demonstrated the production of EVs by trophozoytes of A. castellanii under homeostasis and nutritional stress and characterized their protein content [34,35]. The authors determined the lipid and protein content of these vesicles secreted by the amoebae incubated at 28 • C, temperature in which amoebae behave as free-living organisms.…”
Section: Discussionmentioning
confidence: 94%
“…Except for the population of 50.29 ± 8.49 nm, the size of the EVs obtained in both cases was similar to those reported in the two previous published studies to date, although these were performed using Acanthamoeba of the genotype T4. For example, in 2018, de Souza Gonçalves et al [34] reported EVs of Acanthamoeba castellanii of 117.1 ± 73.3 nm in amoebae incubated in PYG medium and EVs of Acanthamoeba castellanii of 117.7 ± 55.8 nm in amoebae incubated in a glucose medium (under nutritional stress). More recently, Lin et al [35] reported mean diameters of 166.7 nm in the EVs of the same strain of Acanthamoeba.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of parasitic protozoa began in the 17th century (Cox, 2002 ) and, at the least, there are about 90 etiologic species of important human parasitic diseases (Coakley et al, 2015 ), while several other species affect economically important animals (Taylor, 2000 ). Pathogenic and amphizoic protozoa (Gonçalves and Ferreira, 2019 ) are dispersed within phyla amoeba, apicomplexa, metamonada, parabasalia and kinetoplastida (Szempruch et al, 2016a ), which are known to cause a wide range of important diseases such as amoebiasis, malaria, babesiosis, toxoplamosis, leishmaniasis, trypanosomiasis, cryptosporidiosis, trichomoniasis, giardiasis, neosporosis, theileriosis, etc. Over the years, there have been continuous investigations on protozoan parasites' sub-cellular components, organellar structures, secretory/excretory molecules, and, recently, extracellular vesicles (Yanez-Mo' et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%